Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1097/01.rhu.0000191217.11688.3c
|View full text |Cite
|
Sign up to set email alerts
|

Wegener Granulomatosis With Massive Intracerebral Hemorrhage

Abstract: Wegener granulomatosis (WG) is a multisystem necrotizing vasculitis that primarily involves the upper and lower respiratory tract and kidneys but can affect almost any organ, including the central nervous system (CNS). We present a patient with WG whose disease was complicated by a massive intracerebral hemorrhage (ICH) despite standard treatment with prednisone and cyclophosphomide. Although CNS involvement is not uncommon in WG, ICH is a rare complication of WG, and although the majority of patients with WG … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
1
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 16 publications
0
15
1
2
Order By: Relevance
“…Mucosal hemorrhage in the lungs and gastrointestinal tract is frequent complication of small vessel vasculitides including WG, but much less common are intracerebral and intraventricular hemorrhage. ICH may occur as an initial manifestation or latter in the disease course despite being on standard immunosuppressive therapy as our patient [2,6]. This case also demonstrates that the development of CNS vasculitis may correlate with disease activity in other organs such as diffuse pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Mucosal hemorrhage in the lungs and gastrointestinal tract is frequent complication of small vessel vasculitides including WG, but much less common are intracerebral and intraventricular hemorrhage. ICH may occur as an initial manifestation or latter in the disease course despite being on standard immunosuppressive therapy as our patient [2,6]. This case also demonstrates that the development of CNS vasculitis may correlate with disease activity in other organs such as diffuse pulmonary hemorrhage.…”
Section: Discussionmentioning
confidence: 53%
“…Neurologic involvement occurs in 22-54% of patients with WG. It usually manifests as mononeuritis multiplex and polyneuritis; however, CNS involvement (7-11%) is uncommon in WG and ICH as a complication has been rarely reported [1][2][3][4][5].…”
Section: Discussionmentioning
confidence: 99%
“…Cerebral haemorrhage, in particular, is anecdotally reported [18,19], whereas ischemic cerebrovascular events secondary to vasculitis, seizures, diffuse encephalopathy, pituitary gland involvement, chronic hypertrophic pachymeningitis and cranial neuropathies are the most common manifestations [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…Noninferiority of rituximab over cyclophosphamide was proven in the RAVE trial, a multicenter, randomized, double-blind, noninferiority study (grade 1A) [134], and it has also shown efficacy in a few patients with neurological involvement [135,136].…”
Section: Antineutrophil Cytoplasmic Antibody-positive Vasculitidesmentioning
confidence: 99%